A study to assess premature mortality and years of potential life lost among the mortality victims of Victoria Hospital, Bengaluru - Alalageri, Kavya M.; ., Shobha; Sobagaih, Ranganath Timmanahalli (International Journal Of Community Medicine And Public Health, 2017)
Background: Premature mortality by age 60 accounted for one-third of total deaths in low and middle income countries in 2008. While under-5 mortality as a proportion of premature mortality remains high in some countries, premature adult mortality is also increasing. Non-communicable diseases (NCDs) are the leading cause of death and primarily affect those of productive age. India is also experiencing rapid demographic and epidemiological transition. Although evidence suggests recent reductions in infant and child mortality, little is known about the age and sex patterns of premature deaths in India. Methods: Record based study was conducted from 4 months mortality statistics who belong to less than 69 yrs during the period June-September 2016 at Victoria Hospital. Data is entered in MS-Excel and analyzed in the form of descriptive statistics. Data is presented in the form of figures, tables, charts and percentages wherever necessary. Results: There were total of 1265 deaths in 4 months, among them 890 deaths occurred <69 yrs of age. Most of them belong to 45-54 yrs which is the income generating age-group. Most of them belong to 45-54 yrs which is the income generating age-group. Most of the mortality victims admitted in hospital for <24 hrs (45.28%) followed by a week (45.05%). Infectious diseases, burns, hypertension, and alcohol related complications and poly trauma are the top 5 causes of premature deaths. Mean years of potential life lost (YPLL) due to NCDs like cardiovascular diseases, diabetes mellitus and hypertension is 20.92 yrs. Conclusions: Health system should gear up at all levels of health care in order to reduce mortality due to NCDs and thus to increase life-expectancy.